Stem cells in end-to-side neurorrhaphy. Experimental study in rats - Paiva,Geruza Rezende (2020)
Abstract Purpose: To evaluate the influence of mesenchymal stem cells from adipose tissue in the end-to-side neurorrhaphy, focusing in the nerve regeneration and the muscle reinnervation in acute trauma. Methods: 140 animals were randomly divided in seven groups: control, denervated, end-to-side neurorrhaphy between distal stump of common peroneal nerve and tibial nerve (ESN), ESN wrapped in fascia, ESN wrapped in fascia and platelet gel, ESN wrapped in platelet gel, ESN wrapped in fascia and platelet gel within stem cells (without culture) removed from the adipose tissue. Mass measurements of the animal and of cranial tibial muscles, electromyography, walking track analysis tests and histological examinations of the nerves and muscles after 180 days was performed. Results: In the groups where the ESN was performed, the results were always better when compared to the denervated group, showing reinnervation in all ESN groups. The most sensitive methods were walking track and histological analysis. Only the group with stem cells showed values similar to the control group, as well as the functional indices of peroneal nerve and the number of nerve fibers in the peroneal nerve. Conclusions: Stem cells were effective in ESN according with the functional index of the peroneal nerve, evaluated by walking track analysis and the number of nerve fibers in the peroneal nerve.